Different Proposed Models to Mapping MDA to RUP - Mehdi Yaghoubi; Mahmood Yaghoubi; Manoocher Babanezhad (International Journal of Electrical and Computer Engineering (IJECE), 2013)
Reducing of the production expenses and preventing software intricacies is one of the software engineering aims. So, many method and methodology such as object-oriented, component-oriented, aspect-oriented, and service-oriented are preferred for developing software engineering. Model driven development is one of the methodologies that had considered recently and is growing rapidly .modeling the program logic and then changing model to a practicable code by some tool automatically will be the aim of the model driven development. In this paper we investigate some model driven methodology and also we’ll preferred MDA mapping to RUP.DOI:http://dx.doi.org/10.11591/ijece.v3i3.2240